2013
DOI: 10.1126/scisignal.2004125
|View full text |Cite
|
Sign up to set email alerts
|

PLC-γ and PI3K Link Cytokines to ERK Activation in Hematopoietic Cells with Normal and Oncogenic Kras

Abstract: Oncogenic K-Ras proteins, such as K-RasG12D, accumulate in the active, guanosine triphosphate (GTP)–bound conformation and stimulate signaling through effector kinases. The presence of the K-RasG12D oncoprotein at a similar abundance to that of endogenous wild-type K-Ras results in only minimal phosphorylation and activation of the canonical Raf–mitogen-activated or extracellular signal–regulated protein kinase kinase (MEK)–extracellular signal–regulated kinase (ERK) and phosphoinositide-3 kinase (PI3K)–Akt–ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 65 publications
3
18
0
Order By: Relevance
“…Specifically, mutants of K-Ras and B-Raf such as K-Ras(G12D) and B-Raf(V600E) have been extensively studied with regard to their contributions to colon and breast cancer, melanoma, and leukemia DiazFlores et al 2013). The oncogenic activity of K-Ras(G12D) is due to its maintenance of the GTP-bound (active) conformation, which results in the persistent activation of downstream kinase cascades such as Raf-MEK-ERK and PI3K-Akt-mTOR signaling pathways (Diaz-Flores et al 2013). Recent studies with leukemia stem cells and differentiated bone marrow cells have revealed that phospholipase C-γ and PI3K mediate activation of the K-Ras-dependent ERK signaling pathway initiated by cytokine receptors, suggesting that such receptors and proteins upstream K-Ras may be possible therapeutic targets (Diaz-Flores et al 2013).…”
Section: Mapk Signaling In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, mutants of K-Ras and B-Raf such as K-Ras(G12D) and B-Raf(V600E) have been extensively studied with regard to their contributions to colon and breast cancer, melanoma, and leukemia DiazFlores et al 2013). The oncogenic activity of K-Ras(G12D) is due to its maintenance of the GTP-bound (active) conformation, which results in the persistent activation of downstream kinase cascades such as Raf-MEK-ERK and PI3K-Akt-mTOR signaling pathways (Diaz-Flores et al 2013). Recent studies with leukemia stem cells and differentiated bone marrow cells have revealed that phospholipase C-γ and PI3K mediate activation of the K-Ras-dependent ERK signaling pathway initiated by cytokine receptors, suggesting that such receptors and proteins upstream K-Ras may be possible therapeutic targets (Diaz-Flores et al 2013).…”
Section: Mapk Signaling In Cancermentioning
confidence: 99%
“…The oncogenic activity of K-Ras(G12D) is due to its maintenance of the GTP-bound (active) conformation, which results in the persistent activation of downstream kinase cascades such as Raf-MEK-ERK and PI3K-Akt-mTOR signaling pathways (Diaz-Flores et al 2013). Recent studies with leukemia stem cells and differentiated bone marrow cells have revealed that phospholipase C-γ and PI3K mediate activation of the K-Ras-dependent ERK signaling pathway initiated by cytokine receptors, suggesting that such receptors and proteins upstream K-Ras may be possible therapeutic targets (Diaz-Flores et al 2013). PI3K promotes the survival and migration of cancer cells by generating phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ) (Cheung et al 2011).…”
Section: Mapk Signaling In Cancermentioning
confidence: 99%
“…23 Jak inhibition abrogates GM-CSF-dependent ERK phosphorylation in Kras G12D myeloid cells. 59 These results indicate that other pathways contribute to disease in leukemias with hyperactive RAS signaling. Our work suggests activation of the STAT5 pathway may provide these critical signals in leukemia.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, an intermediate protein could also be involved in the observed G βγ -mediated PKC θ activation. For example, studies by others suggest that the immediate downstream mediator of G βγ is PI3K [57][58][59], which is upstream of the novel PKC [60]. Although further investigation is required to more fully understand the underlying mechanisms, we cannot exclude the possibility that an intermediate effector, such as PI3K or PLC β , may be involved in the G βγ -induced PKC θ activation.…”
Section: Discussionmentioning
confidence: 96%